Chiral‐induced highly efficient NIR–photothermal conversion of perylene diimide@silica nanocapsules for photothermal therapy - Yue Zhao; Fuhao An; Jichao Wu; Haining Li; Xueyu Wang; Lanya Jiao; Ying Kong; Jinghan Zhu; Xun Sun; Xu Li; Miao Wang; Yu Zhang; et al. (Aggregate)
Abstract Photothermal agents (PTAs) with ultra‐high photothermal conversion efficiency (PCE) activated upon near‐infrared (NIR) laser irradiation can heat up and destroy tumor cells under low‐intensity laser excitation to allow safe and efficient tumor therapy. Herein, an organic PTA with an outstanding PCE of 89.6% is developed from rationally designed perylene diimide (PDI) with electron‐donating cyclohexylamine moiety at the bay‐positions of its skeleton and chiral phenethylamine (PEA) moiety at its N terminals, termed here PEAPDI. The strong intermolecular interaction between the PDI skeletons induced by PEA together with the intramolecular charge transfer from cyclohexylamine to PDI skeleton severely quenches the fluorescence emission from PEAPDI and significantly enhances its NIR absorption, resulting in super NIR–photothermal conversion. PEAPDI molecules are subsequently encapsulated within silica nanocapsules (SNCs), creating PEAPDI@SNC. Characterized by its small hydrodynamic diameter, monodispersity, high PDI encapsulation efficiency, colloidal stability, and biocompatibility, PEAPDI@SNC exhibits prolonged blood circulation and enhanced permeability and retention effect, enabling targeted accumulation at the tumor site. An in vivo study using a 4T1 tumor–bearing mice model illustrates the agent's potent tumor ablation capability without side effects at low dosage under NIR laser irradiation (808 nm). The findings demonstrate PEAPDI@SNC's significant potential as a PTA for tumor treatment.